Desarrollo de briquetas de borra de café y un aglomerante a diferentes composiciones porcentuales para ser utilizadas como combustible sólido alternativo (2020)
An accessible residue was used in coffee production such as coffee scrub, which was implemented as raw material in the production of briquettes that are burned in a muffle to generate heat energy, being a substitute for other traditional solid fuels (wood and charcoal). In addition, a binder was used for the production of the briquette, because there was no press capable of generating enough pressure to agglomerate coffee scrub alone, thanks to an initial characterization of the raw materials, it was possible to select the suitable binder for this case, the binder chosen was cassava starch, due to the physicochemical properties that were evidenced throughout the project. The different compositions of the briquettes were formulated through a design of mixing experiments, this determined that ten coffee erase briquettes and cassava starch had to be made to different percentage compositions. The ten briquettes were produced and subsequently their physico-chemical properties were determined, showing that the briquette number 2 and 1 generated calorific values of 18.01 and 18.04 MJ/Kg, respectively these being the briquettes with the highest calorific value of the study, however, the briquette number two is considered to be the best in the study, because it has a more solid structure, which allows you to be considered as the best alternative to be a solid biofuel originating from coffee scrubbing.